Early life growth of the white spotted rabbitfish, Siganus canaliculatus (Park, 1797) in Palompon, Leyte, Philippines inferred from otolith microstructure - Guarte, Donna M. (Miagao, Iloilo University of the Philippines-Visayas, 2015)
Early life growth of fish is important in understanding their population dynamics, such taht even a small difference in earlu growth and survival rates can affect the number of recruits entering the adult stock. This study was conducted to examine the early life growth history in its role in the population dynamics of the white spotted rabbitfish Siganus canaliculatus (Park, 1979) in Palimpon, Leyte, Philippines. Specimens were collected monthly for one year, June 2011-May 2012, using sled trawl, spear gun, fish corral and drive-in gill net. Sagital otoliths were processed and analyzed for age and growth using the free image J image processing program. Back-calculation analysios and results from the trawl survey show that S. canaliculatus spawn year-round, with larvae hatched in the minor spawning months (July-November) being more rubost than larvae hatched in the major spawning months (february-May). Larvae in the minor peak of spawning showed faster pelagic and benthic growth rates, shorter pelagic larval durations (PLD). and larger sizes at age (size at settlement and at 1st 37 days), while larvae hatched in February-May showed slower growth rates, smaller sizes at age and prolonged PLDs. The overall robust condition in the minor spawning months could be attributed to generally favoirable southwesterly winds which disperse food organisms towards nearshore habitats, resulting in fast growth, and the transport of larvae from pelagic to benthic habitats, resulting in shortened PLDs and reduced predation risk, and hence high survival. This overall robust condition exhibited by larvae hatched during the minos spawning months is expected to provide survival benefits in the benthic phase, as indicated by the high density of post-settlers (=survivors) in these months and perhaps to later developmental stages up to the adult stage.
Thesis (Master of Science in Biology) -- Miagao, Iloilo : University of the Philippines Visayas, December 2015.
Keywords: White-spotted rabbitfish, Siganus canaliculatus (Park 1797) -- Palompon, Leyte; Palompon, Leyte